Sosialisasi Konvensi Hak Anak (KHA) untuk Mencegah Tindak Kekerasan Kepada Anak di Desa Talang Ipuh, Kabupaten Banyuasin - Yulasteriyani; Diana Dewi Sartika; Gita Isyanawulan (Nawadeepa: Jurnal Pengabdian Masyarakat, 2023)
This service activity aims to 1) provide participants with an understanding of the Convention on the Rights of the Child, 2) reduce acts of violence committed by parents to children, both physical violence and non-physical violence so that children can grow better, and 3) develop positive character without must be subjected to violence. This community service activity is carried out in three stages, namely pre-test, socialization, and post-test. The success of this community service activity can be measured from two achievements, namely 1) all series of community service activities ran smoothly without hindrance, and 2) the concept material for the Convention on the Rights of the Child can be understood and internalized properly by the purpose of community service. The pre-test and post-test results showed an increase in the participants' knowledge and experience regarding the Convention on the Rights of the Child in preventing violence against children.